2015
DOI: 10.1002/gps.4277
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol and sudden cardiac death in dementia: autopsy findings in psychiatric inpatients

Abstract: Autopsy data suggest that oral haloperidol is not associated with increased risk of sudden cardiac death in psychiatric inpatients with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In dementia psychotic symptoms are frequent and occur mostly in the moderate phase. Halucinations and delusions are the componenets of the chalenging behaioour and requaring admission and treatment with antipsychotics and institutionalization [15,16].…”
Section: Resultsmentioning
confidence: 99%
“…In dementia psychotic symptoms are frequent and occur mostly in the moderate phase. Halucinations and delusions are the componenets of the chalenging behaioour and requaring admission and treatment with antipsychotics and institutionalization [15,16].…”
Section: Resultsmentioning
confidence: 99%
“…The low toxicity of haloperidol makes it less of a priority in psychiatric treatment research than other psychomimetic drugs because it is rarely linked to sudden deaths in conditions such as dementia [35].…”
Section: Discussionmentioning
confidence: 99%
“…A review of major cardiac adverse events associated with antipsychotic agents found no clinically significant difference between conventional and atypical agents . In 1 study, autopsy data also suggested that haloperidol is not associated with sudden death in dementia patients . However, 1 retrospective study found a greater relative risk associated with conventional antipsychotics, as did 3 reviews of observational studies .…”
Section: Adverse Events and Excess Mortality Associated With Antipsycmentioning
confidence: 99%
“…68 In 1 study, autopsy data also suggested that haloperidol is not associated with sudden death in dementia patients. 69 However, 1 retrospective study found a greater relative risk associated with conventional antipsychotics, 70 as did 3 reviews of observational studies. 64,66,71 One of these found that hip fracture, stroke, myocardial infarction, and ventricular arrhythmia are among the factors that explain the mortality difference between conventional and atypical agents.…”
Section: Adverse Events and Excess Mortality Associated With Antipsycmentioning
confidence: 99%